(untitled) (Research, Society and Development, 2024)
This report aims to describe a clinical case of complications arising from an accident involving the venom of the caterpillar of the genus Lonomia oblíqua in a 73-year-old male patient who developed disseminated intravascular coagulopathy and acute dialytic renal injury as consequences of the poisoning. Clinical, epidemiological, and laboratory data were collected from the electronic medical records of the patient at the Institution. The patient underwent intensive treatment, initially with the administration of antilonomic serum, treatment of the coagulation disorder, in addition to renal replacement therapy with hemodialysis, with improvement of the coagulation disorder and maintenance on dialytic therapy. Foundation studies for this work point to the nephrotoxic potential and inducer of alterations in homeostatic patterns resulting from contact with Lonomia venom, as noted in the reported case. The importance of rapid management in the treatment of the victim is emphasized, mainly with the prompt administration of antilonomic serum, in order to avoid worse prognoses.